Sustainable Agriculture Reviews 61 Biochar to Improve Crop Production and Decrease Plant Stress under a Changing Climate - Fahad, Shah.; Danish, Subhan; Datta, Rahul; Saud, Shah.; Lichtfouse, Eric. (Cham : Springer International Publishing : Imprint: Springer, 2023)
The book aim to contribute the latest understandings of physiological, biochemical and molecular bases of the responses of major crop plants to a range of different biomass produced biochar to introduce climate resilience crop varieties which leads to enhanced crop productivity and quality under stressful conditions and also for better utilization of natural resources to ensure food security through modern breeding. Finally, this book will be a valuable resource for future plant stress related research with biochar, and can be considered as a reference book for front-line researchers working on sustaining crop production under climate change. Adverse effects of climate changes on crops has developed the situation quite critical for sustainable agriculture. Food security has become in danger due to low production of agricultural crops by resilient climate and ever increasing human population. Heat, drought, salinity, soil compaction, flooding and poor soil organic carbon induced stress in crops by climate adverse conditions are major concerns in this regard. A mechanistic understanding of the interactions between abiotic stresses response of crops is needed to identify and take advantage of acclimation traits in major crop species as a prerequisite for securing robust yield and good quality. This underpins a need for crops with inherent yield increase, yield stability against multiple abiotic stresses and improved quality. Individual stress tolerance mechanisms have been well documented so far. However, mechanisms behind plants' tolerance by application of biochar and its interactions with soil and plant roots towards multiple abiotic stresses are not fully understood. In addition, there will always be some uncertainty associated with modelling the complex relationships between agricultural yields, product quality with biochar under future climate scenarios. Prediction of yield and quality stability, one of most complex agronomic traits, must integrate aspects of plant development, physiology, biochemistry and genetics. Furthermore, the GxExM interactions will complicate the model predications, thus the responses of a given genotype to a defined environment under certain management strategy need to be determined empirically and used to parameterise and refine crop models.
Part 1: Improvement of Crop Yield. 1. Biochar application for improving the yield and quality of crops under climate change (Akbar Hossain) -- 2. Biochar to improve crops yield and quality under a changing climate (Shah Fahad) -- 3. Biochar for improving crop productivity and soil fertility (Fazal Jalal) -- 4. Biochar application to soil to improve fertility (Sadia Zafar) -- Part 2: Alleviation of Plant Stress. 5. Biochar as soil amendment for mitigating nutrients stress in crops (Shah Fahad) -- 6. Biochar to mitigate crop exposure to soil compaction stress (Anis Ali Shah) -- 7. Biochar for mitigation of heat stress in crop plants (Zhixiang Zhang) -- 8. Biochar application to soil for mitigation of nutrients stress in plants (Hafiz Muhammad Rashad Javeed) -- Part 3: Improvement of soil health 9. Biochar from on-farm feedstocks for sustainable potassium management in soils (Hafeez Ur Rahim) -- 10. Biochar for crop protection from soil borne diseases (Rabia Naz) -- 11. Biofertilizers to improve soil health and crop yields (Ligeng Jiang) -- 12. Biochar application to soils to improve the management of irrigation water (Jackson Nkoh Nkoh) -- 13. Role of biochar in the adsorption of heavy metals (Osman Sonmez) -- Part 4: Microbial interactions. 14. Positive and negative impacts of biochar on microbial diversity (Muhammad Nauman Khan) -- 15. Biochar and arbuscular mycorrhizae fungi to improve soil organic matter and fertility (Hafiz Muhammad Rashad Javeed) -- 16.Biochar feedstocks, synthesis and interaction with soil microorganisms (Sammina Mahmood) -- Index.
Keywords: Earth sciences; Geography; Agriculture; Earth and Environmental Sciences; Agriculture